Determination Of Acrylamide In Banana-Based Snacks And Effect Of Different Maturity Stages On Formation Of Acrylamide In Banana Fritters - Daniali, Gisia (2010)

(untitled)
Malaysians consume considerable amount of fried and baked banana-based snacks, which have potential amount of acrylamide content. This study was carried out to a) determine acrylamide in Malaysian banana based snacks by gas chromatography- mass spectrometry, b) to study the effect of maturity stages of banana on the formation of acrylamide in banana fritters. The modified method was based on extraction with water followed by cleanup through Oasis HLB and MCX solid-phase extraction cartridges. Then it was followed by bromination (2.5 mL, saturated bromine water treatment) of acrylamide into 2, 3-dibromopropionamide prior conversion to 2-bromopropenamide by dehydrobromination with triethylamine. The results indicated that volume of 2.5 mL bromine water was sufficient to derivatize the acrylamide. The limit of detection (LOD) and limit of quantitation (LOQ) of the modified method were 5 and 15 μg/kg, respectively, whereas the recovery for 2.5 mL of saturated bromine water ranged from 86.6 to 105.3%. Five types of Malaysian popular fried and baked banana based snacks purchased from different local markets had acrylamide at the range from 74.0 to 7468.8 μg/kg for banana fritter (pisang goreng), 28.9 to 243.7 μg/kg for banana chips (kerepek pisang), 160.7 to 500.4 μg/kg for sweet banana chips (kerepek pisang manis), >5 to 154.4 μg/kg for banana cake (kek pisang) and 31.7 to 609.1 μg/kg for banana balls (cekodok pisang). Analysis of variance showed significant differences (p < 0.05) between acrylamide concentrations in foods from different types. The highest acrylamide content was found in the banana fritter might be related to the higher heating temperature and duration of heating time. To study the effect of maturity stages of banana on the formation of acrylamide in banana fritters, two varieties of local banana Musa paradisiaca variety Awak and Abu were fried before acrylamide determination. The more mature banana had significantly (p < 0.05) higher concentrations of reducing sugars; however, the concentrations of amino acids at different maturity stages were relatively similar (p > 0.05). The study indicated that reducing sugar had significant (p < 0.05) and strong correlation (R2= 0.92 for Abu) and (R2= 0.82 for Awak) with the acrylamide formation, as compared to asparagine. Concentration of acrylamide in both banana varieties enhanced with the increase of both reducing sugars (glucose and fructose). This is demonstrated that the formation of acrylamide presented a strong dependence on the concentration of reducing sugar. However this study failed to show the correlation between acrylamide formation and asparagine as its precursor.